2021
DOI: 10.3390/risks9110192
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning (ML) Technologies for Digital Credit Scoring in Rural Finance: A Literature Review

Abstract: Rural credit is one of the most critical inputs for farm production across the globe. Despite so many advances in digitalization in emerging and developing economies, still a large part of society like small farm holders, rural youth, and women farmers are untouched by the mainstream of banking transactions. Machine learning-based technology is giving a new hope to these individuals. However, it is the banking or non-banking institutions that decide how they will adopt this advanced technology, to have reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Besides these traditional models, some recent researches have used machine learning to utilize all data available and systematic models that are accurate, efficient, and objective. In term of credit scoring, Kumar et al (2021) use systematic literature review methods to identify and compare the best fit AI-ML-based model adopted by various financial institutions worldwide. The main purpose of this study is to present the various ML algorithms highlighted by earlier researchers that could be fit for a credit assessment of rural borrowers, particularly those who have no or inadequate loan history.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Besides these traditional models, some recent researches have used machine learning to utilize all data available and systematic models that are accurate, efficient, and objective. In term of credit scoring, Kumar et al (2021) use systematic literature review methods to identify and compare the best fit AI-ML-based model adopted by various financial institutions worldwide. The main purpose of this study is to present the various ML algorithms highlighted by earlier researchers that could be fit for a credit assessment of rural borrowers, particularly those who have no or inadequate loan history.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In some circumstances, artificial intelligence and digital labor can be used to support development of rural areas. For example, Kumar et al (2021) found that machine learning technologies could facilitate digital credit scoring in rural finance so that people living in rural areas were more likely to access to financial services. In fact, people living in rural areas usually have limited access to financial services and goods.…”
Section: Economic Resource Allocation Between Regionsmentioning
confidence: 99%
“…We propose a gendersensitive risk analysis model, speci cally targeting impoverished and vulnerable women, using AI within the framework of complex thinking to achieve the nancial inclusion of an under-nanced population segment through formal nancial institutions. Our proposal differs from others because the specialized literature on the subject (Kumar et al, 2021b;Akter et al, 2021) points to the need for new variables that integrate gender, poverty and vulnerability, and entrepreneurship to create speci c products and services but do not contemplate complex thinking; although some models use AI and consider the clients' contextual complexity, they do not include the framework of complex thinking.…”
Section: Introductionmentioning
confidence: 99%
“…Low-income people do not necessarily have higher credit risks than the banked population because they can transform the three basic types of available resources (physical capital, human capital, and social capital) into assets to improve their quality of life. Currently, AI and machine learning-based technologies have designed new ways to do credit scoring from customer characteristics (the complete pro le of the borrower's current income level, employment opportunities, and potential ability to repay the loan) (Kumar et al, 2021;Kumar et al, 2021b); also, there are non-traditional combinations of various models and algorithms to design better options for credit scoring (Papouskova and Hajek, 2019;Xu et al, 2020;Liu et al, 2022). New models have improved the statistical performance of credit rating models, some incorporating alternative data sources such as calls made from cell phones, mobile device ngerprints, e-commerce, social networks, email, psychometric variables, and the integration of public and mobile geospatial data from satellites; that is, non- This article proposes a comprehensive solution to promote access and permanence in the entrepreneurial ecosystem for women who run micro businesses and are in a situation of poverty and vulnerability in Mexico.…”
Section: Introductionmentioning
confidence: 99%